Коллекция средневекового стекла из раскопок г. Тигранакерт в Арцахе - Варданесова, Татьяна (Հայաստանի պատմության թանգարան)
The collection of medieval glass from Tigranakert city in Artsakh consists of 1545 items. Fragments of medieval glassware were found in the cultural layers of the 5th – 7th, 9th – 11th and 12th – 13th centuries in the Central District, as well as in the 12th – 13th century layer in the Fortified District. It should be noted, that the remains of glass production – the furnace and the stone smelter for glass – were opened in the excavation of the Medieval Square in the Central District. This indicated on the local production of glass. The furnace is round laid out from bricked in 5 rows: the bricks are burnt, many are broken in to half. The inner diameter of the furnace is 0.78 m. The inside of the furnace was filled with pieces of brick and tiles. This glass workshop probably belonged to the type where the glass was not boiled, but processed by melting pieces of glass. The small pieces of such glass were found in the excavation site. Judging by the excavation layer, it belonged to the early medieval period. The operating time of a similar furnace is limited by the 5 – 6 years, but the tradition of glass production was preserved later. So, manufacturing defects from glass bracelets production were found in the layers of the 11th – 12th centuries. The whole mass of glass objects, according to the meaning of their use, can be divided into two groups: jewelry (bracelets and beads) and vessels, among which a group of oil lamps can be distinguished. Unfortunately, no complete vessels have been found and the glass fragments sometimes are quite small, so through them it is difficult to understand the shape and use of the vessels. Արցախի Տիգրանակերտ քաղաքի միջնադարյան ապակյա իրերի հավաքածուն բաղկացած է 1545 միավորից։ Միջնադարյան ապակյա իրերի բեկորները հայտնաբերվել են Կենտրոնական թաղամասի 5 – 7-րդ, 9 – 11-րդ և 12 – 13-րդ դարերի մշակութային շերտերում, ինչպես նաև Ամրացված թաղամասի 12 – 13-րդ դարերի շերտում։ Հարկ է նշել նաև, որ Կենտրոնական թաղամասում վաղմիջնադարյան հրապարակի վրա բացվել են ապակու արտադրության մնացորդները՝ հնոցը և քարե հալոցը ապակու համար։ Սա վկայում է ապակու տեղական արտադրության մասին։ Կլոր վառարանի փոսը աղյուսապատված է 5 շարքով՝ աղյուսները թրծած են, շատերը ջարդված են։ Հնոցի ներքին տրամագիծը 0,78 մ է։ Հնոցի ներսը լցված էր աղյուսի և կղմինդրի կտորներով։ Հավանաբար, այս արհեստանոցը պատկանում էր այն տեսակին, որտեղ ապակին ոչ թե եփվել, այլ վերամշակվել էր՝ հալեցնելով արդեն իսկ պատրաստի ապակու կտորները։ Պեղավայրում ապակու խարամի հետ հայտնաբերվել են նման ապակու մնացորդներ՝ ոչ մեծ կտորներով։ Դատելով պեղման շերտից՝ այն պատկանում էր վաղմիջնադարյան ժամակաշրջանին։ Նմանատիպ հնոցի շահագործման ժամանակը սահմանափակ է՝ 5 – 6 տարի, սակայն ամենայն հավանականությամբ ապակու արտադրության ավանդույթը պահպանվել է նաև հետագայում։ Ավելի ուշ՝ 11 – 12-րդ դարերի շերտերում գտնվել են ապակե ապարանջանների արտադրական խոտանները։ Ապակե իրերի ողջ զանգվածը, ըստ իրենց կիրառման նշանակության, կարելի է բաժանել երկու խմբի՝ զարդեր (ապարանջաններ և ուլունքներ) և անոթներ, որոնց մեջ կարելի է առանձնացնել ղամպարների խումբը։ Ցավոք, ամբողջական անոթներ չեն հայտնաբերվել, և բեկորները երբեմն բավականին փոքր են։ Նրանց միջոցով դժվար է հասկանալ անոթի ձևը։
Keywords: Археология